HANDBALL DRIBBLING LEARNING MODEL FOR JUNIOR HIGH SCHOOL STUDENTS - Rusmiyadi, Rusmiyadi (Cakrawala Pedagogik, 2024)
The purpose of this research and development is to produce a handball dribbling learning model for junior high school students. In addition, this research and development was conducted to obtain in-depth information about: improving motor skills in vocational high school students and to determine the level of success of developing a handball dribbling model in terms of: effectiveness, efficiency, attractiveness, and productivity of students in dribbling handball in junior high school students. This research and development uses a qualitative approach and uses the Borg W. R and Gall. MD Research and Development (R & D) development method. The subjects in this research and development were 60 vocational high school students. The instruments used in this research and development were questionnaires, questionnaires, and handball dribbling psychomotor instruments used to collect data at the stages: (1) needs analysis; (2) expert evaluation (initial product evaluation); (3) vocational trial (small group trial); and (4) main trial (field testing). The effectiveness test of the model used a handball dribbling psychomotor test, while to see the results of the effectiveness of the model, a statistical test was used using the before-after formula (pre-test and post-test). The results of the pre-test calculation obtained a result of 780 with an average of 50.30 while the post-test obtained a result of 810 with an average of 52.75, this means that the handballg dribbling learning model is better than the conventional learning model. Based on the results of the development, it can be concluded that: (1) With the handball dribbling learning model, students can learn effectively and efficiently. (2) With the handball dribbling learning model that researchers have developed, students can improve their motor skills in the learning process.